"Ein linientreuer Dissident" : Memoiren 1945 - 1989 - Kuczynski, Jürgen 1904-1997 (Aufbau-Verl, 1992)
Jürgen Kuczynski: "Ein linientreuer Dissident". Memoiren 1945-1989. Aufbau-Verlag, Berlin 1992. 434 S., geb., 39,80 DM